2023
DOI: 10.1186/s12877-023-03791-8
|View full text |Cite
|
Sign up to set email alerts
|

Living arrangement of Indian elderly: a predominant predictor of their level of life satisfaction

Abstract: Objective This article aims to examine the level of life satisfaction (LS) among Indian older adults and to determine whether their living arrangement is one of the potential determinants of their level of LS. Methods Data was drawn from the first and most recent wave of Longitudinal Ageing Study in India conducted in 2017–18. Using the Satisfaction with Life Scale, the level of LS was assessed for 30,370 elderly aged 60 + . Bivariate analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“… Quashie et al (2022) found that co-residing male seniors were less likely to receive health support from offspring during illness than their female counterparts. Sun and Zimmer (2022) and Kandapan et al (2023) both established that residing with children enhanced life contentment in older adults. In addition to research related to blood relatives such as children and grandchildren, Researchers from both India and Pakistan have observed that widowed and solitary elderly individuals face a more than 50% increased likelihood of depression compared to their married and cohabiting counterparts ( Bhamani et al, 2013 ; Srivastava et al, 2021 ).…”
Section: Introductionmentioning
confidence: 97%
“… Quashie et al (2022) found that co-residing male seniors were less likely to receive health support from offspring during illness than their female counterparts. Sun and Zimmer (2022) and Kandapan et al (2023) both established that residing with children enhanced life contentment in older adults. In addition to research related to blood relatives such as children and grandchildren, Researchers from both India and Pakistan have observed that widowed and solitary elderly individuals face a more than 50% increased likelihood of depression compared to their married and cohabiting counterparts ( Bhamani et al, 2013 ; Srivastava et al, 2021 ).…”
Section: Introductionmentioning
confidence: 97%
“…Because of things like family structure and connections, a study has shown that older people who live with their spouse and children have greater life satisfaction than those who live alone ( Kooshiar et al, 2012 ). Kandapan et al found that older people’s living arrangements in India substantially impacted how satisfied they felt with their lives ( Kandapan et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%